Validación del torque de doblez de una barra o tubo por compresión mediante el uso del método de elementos finitos (2020)
In order to reduce test-related costs and increase process efficiency, an alternative way to experimentation is proposed to validate the bending torque in tubes and bars by compression, bearing in mind that this is one of the parameters that provides greater control in the process. The modeling torque value was higher than the theoretical torque value that corresponds to the adapted analytical model, taking into account the fact that the analytical method did not take into account variables that were involved in the compression bending process such as friction that in the end will have an effect on the increase of the applied force.